Integrated CFD–drying model for design optimisation of multi-layer rack drying systems for mackerel processing - Nabudda, Kriengkrai; Thasnas, Natakorn; Poungthong, Pongthep (My University, 2026)
This study presents an integrated Computational Fluid Dynamics (CFD)–Page model framework for analysing and optimising the drying performance of a six-layer mackerel drying system. Experimental drying data were fitted using the Page model (k = 0.185, n = 1.32), achieving high predictive accuracy (RMSE = 0.018). The coupled CFD–drying model was applied to evaluate moisture removal behaviour and the effect of rack spacing on airflow distribution, temperature uniformity, and heat transfer. Results revealed distinct layer-dependent drying characteristics, with the uppermost layer exhibiting the fastest moisture removal due to greater exposure to hot, low-humidity airflow. CFD simulations for rack spacings of 8–12 mm showed that spacing significantly influences airflow penetration and thermal distribution. A mesh-independent model with 261,785 elements ensured numerical reliability. The optimal rack spacing was identified as 10 mm, providing the most uniform airflow and temperature distribution. Surrogate model optimisation further predicted an optimal spacing of 10.21 mm, improving drying uniformity, energy efficiency, and overall system performance.
Keywords: CFD modelling; Engineering design optimisation; Heat and mass transfer; Mackerel drying; Multi-layer rack optimisation